MATURE TESTICULAR TERATOMA IN PEDIATRIC PATIENT: A CASE REPORT - Indra Firdaus, Gugum; Ismy, Jufriady (Indonesian Journal of Urology, 2022)
Objective: To report our experience on management of testicular teratoma in pediatric patient. Case(s) presentation: A 2-years-old boy presented with progressive mass in his left testis. The mass was found 3 months ago but became larger in a few days. The patient had no other genitourinary complaint. Vital signs were within normal limits. A hard and tender mass in the left scrotum sized 5x4x2.5 cm was palpated from the physical examination. An imaging study with Computed Tomography (CT) Scan revealed an enhancement in the left scrotum mass area. There was no ring enhancement in pelvic and paraaortic lymph nodes. The laboratory examination within normal limit. Inguinal radical orchiectomy was performed, and histopathological examination revealed a mature testicular teratoma of the left testis. Discussion: Testicular teratoma in children is usually benign. Testicular germ cell tumors generally have a good prognosis with current therapy. Post-orchiectomy management depends on the histology type, staging, and tumor markers. Conclusion: Testicular teratoma is a rare case and can cause minimal symptoms until it grows significantly. Testicular teratoma should be considered in the differential diagnosis of non-traumatic painless progressive scrotal mass. Inguinal radical orchiectomy may be considered as the primary management.